Sludge dewatering method based on coupling of modified coal cinder and multivalent ferric salt
Through the combined conditioning method of ferrate and modified cinder, the problems of poor effect of single conditioning agent and excessive addition in sludge dehydration technology are solved, and the deep dehydration and efficient flocculation of the sludge are achieved, with simple operation and Low cost and environmental protection advantages.
Patent Information
- Application Number
- CN202411573131.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The existing sludge dewatering technology has the problem of poor effect of a single conditioner and excessive addition of the amount, resulting in increased treatment costs. Especially the complex composition of the sludge is difficult to achieve deep dehydration.
The combined conditioning method of ferrate and modified cinder is adopted to coordinate the sludge by oxidizing the ferrate and adsorption capacity of the modified cinder to achieve deep dehydration of the sludge.
This method can significantly reduce the moisture content of the sludge, improve the dehydration and flocculation performance of the sludge, and is simple to operate, low cost, environmentally friendly, and avoid the problem of excessive addition of a single conditioner.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical field:
[0001] The invention relates to the technical field of sludge dehydration, and in particular to a sludge dehydration method based on modified coal slag coupled with multivalent iron salt. Background technology:
[0002] In recent years, the composition of sludge has become increasingly complex, the amount of sludge has increased, and the effective disposal rate of sludge is not satisfactory. The negative impact on the ecological environment has become increasingly prominent, which has attracted widespread attention from the society. Sludge dewatering is a very important link in the sludge treatment and disposal process. Sludge dewatering can not only reduce the volume of sludge, but also save the subsequent transportation, treatment and disposal costs of sludge. Therefore, it is of great significance. Several common sludge dewatering technologies in China include flocculation dehydration, mechanical dehydration, drying dehydration, ultrasonic dehydration and electro-osmosis dehydration.
[0003] Sludge is extremely difficult to dehydrate due to the complexity of its composition. A single conditioning agent encounters many problems in the process of sludge dehydration. For example, the moisture content of sludge is still high after FeCl3 conditioning alone, and its dosage is too large; although modified coal slag can effectively reduce the moisture content of sludge, the excessive dosage makes the subsequent treatment of sludge cake more difficult; although ferrate pre-conditioning can effectively break the EPS of sludge, the dosage is too small, which weakens the flocculation degree of sludge. If the dosage is increased, the treatment cost will increase. This is because different conditioning agents have different structures and modes of action. Using them alone can no longer meet the needs of actual production. Using multiple conditioning agents to condition sludge can utilize the advantages of various conditioning agents to a certain extent. Therefore, the combined use of agents has received widespread attention from researchers.
[0004] Ferrate is a green oxidant with high oxidizing properties. The generated new ecological hydrated iron oxide has good flocculation effect, and has great development prospects in sludge conditioning. The modified products of coal slag can be used for sludge conditioning and can be used as a low-cost conditioning agent. If the two can be used together, it will have both environmental and economic benefits. Summary of the invention:
[0005] Based on the above situation, the present invention provides a sludge dehydration method, which utilizes the modified product of ferrate and coal ash as a sludge dehydration conditioner to achieve deep sludge dehydration. The method has good dehydration effect on the sludge to be treated, is simple to operate, low in cost, and is green and environmentally friendly.
[0006] In order to achieve the above object, the present invention provides a sludge dewatering method on one hand, which respectively examines the effects of conditioning sludge with modified coal slag alone, conditioning sludge with ferrate alone, and conditioning sludge with ferrate and modified coal slag in combination, and comprises the following steps: Description of the drawings:
[0007] Figure 1 The effect of the coal slag of Example 1 of the present invention and the acid- and alkali-modified coal slag on the sludge specific resistance (SS = 12.6 g / L)
[0008] Figure 2 The effect of the coal slag of Example 1 of the present invention and the acid- and alkali-modified coal slag on the sludge moisture content (SS = 12.6 g / L)
[0009] Figure 3 The effect of raw coal slag on sludge settling performance in Example 1 of the present invention (SS = 12.6 g / L)
[0010] Figure 4 The effect of alkali-modified coal ash of Example 1 of the present invention on sludge settling performance (SS = 12.6 g / L)
[0011] Figure 5 The effect of the acid-modified coal slag of Example 1 of the present invention on the sludge settling performance (SS = 12.6 g / L)
[0012] Figure 6 The effect of different coal ash on sludge settling performance in Example 1 of the present invention (SS = 12.6 g / L; coal ash dosage = 24 g / L)
[0013] Figure 7 The effect of different dosing methods on sludge SRF in Example 2 of the present invention (SS = 12.5 g / L)
[0014] Figure 8 The effect of different dosing methods on the sludge moisture content in Example 2 of the present invention (SS = 12.5 g / L)
[0015] Fig. 9 The effect of different dosing methods on sludge settling performance in Example 2 of the present invention (SS = 12.5 g / L)
[0016] Fig.10 The effect of different dosing methods on sludge CST in Example 2 of the present invention (SS = 12.5 g / L)
[0017] Fig.11 The effect of different dosing sequences on sludge SRF in Example 3 of the present invention (SS = 12.5 g / L)
[0018] Fig.12 The effect of different dosing sequences on sludge SCOD in Example 3 of the present invention (SS = 12.5 g / L)
[0019] Fig.13 The effect of different dosages on sludge SRF in Example 3 of the present invention (SS = 12.5 g / L) Specific implementation method:
[0020] The specific implementation modes of the present invention are described in detail below with reference to the accompanying drawings.
[0021] Example 1
[0022] (1) Modified coal slag was used to condition the sludge. The sludge from the sewage treatment plant was conditioned by adding coal slag. The optimal modification conditions of coal slag were determined through orthogonal experiments. The modified coal slag was used to carry out sludge sedimentation and filtration dewatering experiments. The effects of coal slag on the dewatering and sedimentation properties of sludge under different dosage conditions were investigated. The optimal dosage of acid- and alkali-modified coal slag for sludge conditioning was determined to verify its feasibility as a sludge conditioner.
[0023] Table 1
[0024]
[0025] The nine groups of experimental data obtained from the orthogonal experiment of acid-modified coal slag are listed in Table 1. The experimental conditions of the fifth group are: acid concentration of 4 mol / L, acid-ash ratio of 3:1 ml / g, acid leaching time of 3 h. The coal slag obtained is used to condition sludge dehydration, and the obtained sludge specific resistance is the smallest, which is 0.16×1013 m / kg. It can be seen that it is the group of data closest to the optimal modification conditions. According to the analysis of the extreme R value, it can be seen that the order of the influence of various factors on the specific resistance (SRF) from small to large is: acid-ash ratio < acid leaching time < acid concentration, among which the R value of acid concentration and acid leaching time is much higher than the R value of acid-ash ratio.
[0026] Table 2
[0027]
[0028] The orthogonal experimental data of coal slag after alkali modification are listed in Table 2. It can be seen that among the nine groups of experimental data obtained from the orthogonal experiment of coal slag after alkali modification, the experimental conditions of the fifth group are: alkali concentration of 4 mol / L, alkali-ash ratio of 3:1 ml / g, alkali leaching time of 3h, the coal slag prepared is used for conditioning sludge dehydration, and the obtained sludge specific resistance is the smallest, which is 0.21×1013 m / kg, which is the best modification condition. According to the analysis of the extreme R value of alkali-modified coal slag, it can be seen that the order of the influence of various factors on specific resistance (SRF) from small to large is: alkali-ash ratio < alkali leaching time < alkali concentration, among which the R value of alkali concentration and alkali leaching time is much higher than the R value of alkali-ash ratio.
[0029] It can be seen that the acid and alkali concentrations and the acid and alkali immersion time are important factors affecting the alkali modification of coal slag. Through the orthogonal experiment of coal slag modification, the optimal conditions for acid and alkali modification are: modification liquid concentration = 4mol / L; modification liquid to ash ratio = 3:1ml / g; modification liquid immersion time = 3h. In the subsequent sludge dewatering experiment, the effect of modified coal slag on the actual sludge dewatering effect under the above modification conditions was investigated, so as to select the best modification method among the acid and alkali modification methods.
[0030] (2) The change in the performance of coal slag after acid or alkali modification is mainly due to the change in the surface of the coal slag particles. The surface of the unmodified coal slag particles is smooth, and the surface of the coal slag particles after alkali modification becomes rough. After the glass between the acid-modified coal slag particles is dissolved by acid, the originally connected particles are opened, the pores between the particles increase, the surface becomes rougher, the specific surface area increases accordingly, and the adsorption performance is also improved. The specific surface area of the three types of coal slag (original coal slag, alkali-modified coal slag, and acid-modified coal slag) measured by the specific surface area analyzer is 16.7 m 2 / g, 58.9m 2 / g and 119.7m 2 / g. It can be seen that acid-modified coal slag can better improve the adsorption capacity of coal slag.
[0031] After the sludge was conditioned by modified coal ash, the mixed sludge sample was dehydrated by constant pressure filtration under a vacuum degree of 0.03 MPa. The relevant parameters are shown in Table 3.
[0032]
[0033] As can be seen from Table 3, with the increase of different coal slag dosage, the time from sludge added with three kinds of coal slag to filter cake cracking is constantly decreasing. This time has a positive correlation with the sludge specific resistance. The longer the dehydration time, the greater the sludge specific resistance, and vice versa. At a smaller dosage, when the dosage is 8g / L, the cracking time of the original coal slag, alkali-modified coal slag, and acid-modified coal slag is reduced from 2650s to 767s, 512s, and 468s, respectively. When the dosage is further increased to 16g / L, the cracking time is reduced to 323s, 145s, and 131s, respectively. At the same time, the filtrate volume after sludge dehydration is also decreasing, and the filtrate volume is proportional to the sludge dehydration time, that is, the longer the dehydration time, the larger the filtrate volume, and vice versa. When the coal slag dosage is 8g / L, the filtrate volume of original coal slag, alkali-modified coal slag and acid-modified coal slag changes from 91mL to 91mL, 89mL and 85mL respectively; when the dosage is 16g / L, the filtrate volume changes to 89mL, 88mL and 83mL respectively. It can be seen that if the same filtrate volume is achieved, the time required is in the order of acid-modified coal slag < alkali-modified coal slag < original coal slag.
[0034] like Figure 1 After adding raw coal slag, acid-modified coal slag and alkali-modified coal slag, the sludge specific resistance decreased significantly, and the sludge dewatering performance was significantly improved. With the increase of the dosage, the sludge specific resistance decreased first faster and then slower. Although the three different coal slags have a good improvement on sludge dewatering, under the condition of the same dosage, the acid-modified coal slag has the best effect, the alkali-modified coal slag is second, and the raw coal slag is the worst. When the addition amount of coal slag is 8g / L, the sludge specific resistance of original coal slag, alkali-modified coal slag and acid-modified coal slag decreases from the initial 0.78×1013m / kg to 0.7×1013m / kg, 0.56×1013m / kg and 0.43×1013m / kg respectively. When the addition amount increases to 24g / L, the sludge specific resistance changes to 0.52×1013m / kg, 0.32×1013m / kg and 0.24×1013m / kg respectively. With the increase of the addition amount of coal slag and modified coal slag, the sludge specific resistance drops sharply at the initial stage. The reason is that the strength of the newly generated flocs of the sludge increases after conditioning. When mechanical dehydration is used, the number of flocs destroyed by shear force is reduced, which reduces the phenomenon of fine particles in the sludge blocking the filter pores, thereby reducing the filtration resistance and improving the filtration performance. And the effect of using modified coal slag to condition sludge is better than that of using coal slag directly. When using modified coal slag to condition sludge, the sludge specific resistance decreases faster, indicating that the modified coal slag has better enhanced dewatering performance than the original coal slag. When the amount of coal slag added increases from 24g / L to 56g / L, the sludge specific resistance drops to 0.45×1013m / kg, 0.21×1013m / kg, and 0.21×1013m / kg, respectively. With the increase of the amount of modified coal slag added, the trend of the sludge specific resistance value decreasing becomes slow. This may be due to the fact that there is a certain range of resistance changes during sludge filtration. Beyond this range, even if the amount is increased, the change in sludge specific resistance is no longer obvious. At the same time, it also shows that there is an optimal dosage for conditioning sludge with modified coal slag. From the change of sludge specific resistance, the modified coal slag dosage of 24-32g / L is selected as the optimal dosage, at which time the sludge specific resistance is greatly reduced. Therefore, it can be considered that coal ash is an effective sludge conditioner, and the acid-modified coal ash shows better ability to condition and promote sludge dewatering.
[0035] (3) Figure 2The moisture content of the filter cake after filtering and dehydration of the sludge conditioned with different dosages of modified coal slag. With the increase of the dosage of modified coal slag, the moisture content of the filter cake gradually decreases. When the dosage of coal slag is 8g / L, the moisture content of the mud cake of the original coal slag, alkali-modified coal slag, and acid-modified coal slag is reduced from the initial 85% to 82%, 79%, and 76%, respectively. When the dosage is increased to 24g / L, the moisture content of the mud cake changes to 72%, 67%, and 60%, respectively. When the dosage is increased to 56g / L, the moisture content of the mud cake is reduced to 61%, 57%, and 52%, respectively. This is because the sludge contains a large number of tiny particles, and the liquid permeability of the filter cake formed by these tiny particles is relatively poor, because these tiny particles may be deformed during filtration, and the porosity of the formed filter cake gradually decreases. The modified coal slag particles are hard, with a rough surface and strong adsorption. They can play the role of electrical neutralization and adsorption bridging in the sludge, destroying the stability of the sludge colloidal dispersion system, and causing the small particles dispersed in the sludge to aggregate into larger particles. At the same time, the spherical structure of the coal slag increases the porosity of the filter layer and reduces the resistance to water removal from the mud cake. At the same time, since the particle size of the coal slag is smaller than that of the sludge, some of the coal slag particles enter the pores between the sludge particles, causing some interstitial water to be released, thereby improving the dewatering performance of the sludge. After adding coal slag to the sludge, the formation of cavities and channels between the coal slag particles and the sludge particles will also lead to a decrease in the filtration resistance and a faster filtration rate.
[0036] (4) Figure 3 The figure shows the change of sedimentation performance of sludge after conditioning with raw coal slag. The sedimentation performance of sludge is usually used as an indicator of the reaction sludge floc structure and mud-water separation. Improving the sedimentation performance of sludge is conducive to better removal of interstitial water in sludge, improving the solid content of sludge and the efficiency of subsequent mechanical dehydration. It can be seen that with the extension of sludge sedimentation time, the sludge height gradually decreases, the volume of sludge supernatant also increases, and the water content of sludge concentration increases. When no coal slag is added, the sedimentation performance of sludge is poor, and there is almost no particularly clear sedimentation interface. When the amount of coal slag added is 24g / L and the sedimentation time is 50min, the sludge height accounts for 86.5%. To achieve the same sludge height percentage, when the coal slag addition is 16g / L, it takes about 70min, and the amount of coal slag added is 32g / L. It takes about 40min. It can be seen that with the increase of coal slag addition, the sedimentation rate of sludge increases and the sedimentation performance gradually improves. At 30 minutes after the sludge settling, the sludge height ratio decreased from the initial 96.2% to 83.4% corresponding to the slag dosage of 32g / L, and finally to 78.1%, at which the slag dosage was 56g / L. The specific surface area of the original slag increased after modification, and the corresponding adsorption energy also increased. Figure 4The figure shows the change of sedimentation performance of sludge after conditioning with alkali-modified coal slag. It can be seen that the sedimentation speed of sludge modified by alkali is significantly accelerated. When the dosage of alkali-modified coal slag is 24g / L and the sedimentation time is 50min, the sludge height ratio is 84.1%. If the same sludge height ratio is to be achieved, it takes about 60min when the slag dosage is 16g / L, and it takes nearly 35min when the slag dosage is 32g / L. In comparison, the strengthening effect of alkali-modified coal slag on sludge sedimentation performance is better than that of original coal slag. This is because the surface of alkali-modified coal slag is rougher, and the particles themselves are small, which makes it easier to become the crystal nucleus of large flocs, adsorbing and aggregating small particles of sludge flocs together to form large particles of sludge flocs that are easy to settle. Figure 5 The figure shows the change in the settling properties of the sludge after conditioning with acid-modified coal slag. It can be seen that the settling properties of the sludge conditioned with acid-modified coal slag are increased compared with the sludge settling properties of the alkali-modified coal slag, and the trend of the settling curve is similar to that of the original coal slag and alkali-modified coal slag. When the dosage of acid-modified coal slag is 24g / L and the sedimentation time is 50min, the sludge height ratio is 82.5%. If the same sludge height ratio is to be achieved, it takes less than 60min when the coal slag dosage is 16g / L, while the coal slag dosage of 32g / L requires nearly 35min. In comparison, the influence on the sludge settling effect is arranged from large to small as follows: acid-modified coal slag>alkali-modified coal slag>original coal slag. Comparison Figure 3 , Figure 4 , Figure 5 It can be seen that the sedimentation speed of sludge is different under different coal cinders and different dosages. However, after a period of sedimentation, the sludge height ratio is never lower than 50%. This is because the free sedimentation of sludge concentration can only remove the water in free form in the sludge. If more water is to be removed, mechanical dehydration is required. Figure 6The comparison of the sedimentation performance of sludge conditioned by coal slag, alkali-modified coal slag and acid-modified coal slag when the dosage is 24g / L. It can be seen that the addition of appropriate amounts of different coal slags can increase the sedimentation rate, thereby shortening the sedimentation time of the sludge. When the sedimentation of the original coal slag, alkali-modified coal slag and acid-modified coal slag reaches 30min, the sludge height ratio is reduced to 93.3%, 91.6% and 90.1% respectively, and when the sedimentation reaches 60min, the corresponding sludge height ratio is reduced to 85.2%, 82.4% and 79.1%, and when the sedimentation reaches the last 90min, the corresponding sludge height ratio is reduced to 77.4%, 72.7% and 67.4%. This shows that the coal slag has a porous structure, the porosity is generally 60% to 75%, and it has the characteristics of large specific surface area and strong adsorption capacity, but due to the limitations of its own physical and chemical properties, its adsorption performance is not ideal. After the acid and alkali modification of the coal slag particles, SiO2 and Al2O3 on the surface covered by impurities are dissolved, and the number of broken bonds increases, which not only increases the chemical properties of the coal slag, but also increases the specific surface area and reaction contact area, greatly improving the adsorption performance of the coal slag. The modified coal slag has a certain adsorption effect on the soluble organic matter in the sludge system. Through the adsorption effect, the soluble organic matter in the sludge system is separated from the surface of the sludge flocs, so that the original relatively stable sludge floc structure is destroyed and destabilized, and the free water therein is released, thereby improving the sedimentation performance and flocculation performance of the sludge. According to the above analysis, acid-modified coal slag is better than alkali-modified coal slag for sludge dehydration, so acid modification is selected.
[0037] Example 2
[0038] (1) After the sludge was conditioned by four different methods, namely, Fe(III) alone, Fe(III)+Fe(VI), Fe(III)+modified coal slag, and Fe(III)+Fe(VI)+modified coal slag, the mixed sludge sample was dehydrated by constant pressure filtration under a vacuum degree of 0.08 MPa. The relevant parameters are shown in Table 3
[0039]
[0040] Note: The number after the agent represents the dosage
[0041] As can be seen from Table 3, with the increase of the dosage of iron salt, the time for the sludge treated by four different conditioning methods to be filtered until the filter cake cracks continuously decreases. This time has a positive correlation with the sludge specific resistance. The longer the cracking time required, the greater the sludge specific resistance, and vice versa. When the dosage of Fe(III) is 20 mgFe / gSS, the cracking times of Fe(III) alone, Fe(III)+Fe(VI), Fe(III)+modified cinder, and Fe(III)+Fe(VI)+modified cinder decrease from 2650 s, 1820 s, 75 s, and 71 s to 1860 s, 1260 s, 60 s, and 58 s respectively. When the dosage is further increased to 60 mgFe / gSS, the cracking times decrease to 875 s, 434 s, 57 s, and 57 s respectively. At the same time, the volume of the filtrate after sludge dewatering also continuously decreases, and the volume of the filtrate is proportional to the sludge dewatering time, that is, the longer the dewatering time, the greater the volume of the filtrate, and vice versa. When the dosage of Fe(III) is 20 mgFe / gSS, the volumes of the filtrate of the four methods of Fe(III) alone, Fe(III)+Fe(VI), Fe(III)+modified cinder, and Fe(III)+Fe(VI)+modified cinder change from 91 mL, 89 mL, 85 mL, and 83 mL to 90 mL, 88 mL, 80 mL, and 77 mL respectively. When the dosage of Fe(III) is 60 mgFe / gSS, the volumes of the filtrate change to 87 mL, 86 mL, 79 mL, and 75 mL respectively. It can be seen that if the same volume of filtrate is to be achieved, the order of the time required from small to large is: Fe(III)+Fe(VI)+modified cinder < Fe(III)+modified cinder < Fe(III)+Fe(VI) < Fe(III). It can be seen that under the same conditions, the enhanced dewatering effect of modified cinder is better than that of ferrate. This is because the strong oxidizing property of ferrate causes the sludge flocs to disintegrate. Although the bound water is released, it also increases the dewatering difficulty to a certain extent, resulting in a lower dewatering effect than that of modified cinder. However, the combined conditioning of modified cinder and ferrate can achieve the best effect. This dosing method can improve the deficiency of the dewatering ability of ferrate, making the sludge dewatering effect increase significantly.
[0042] (2) Figure 7The effects of four different conditioning methods, namely, Fe(III), Fe(III)+Fe(VI), Fe(III)+modified coal slag, and Fe(III)+Fe(VI)+modified coal slag, on the sludge specific resistance. It can be seen that after the sludge is conditioned in four different ways, the specific resistance has decreased, and the sludge dewatering performance has been significantly improved. When the dosage of Fe(III) is 0, the three methods of Fe(VI), modified coal slag, and Fe(VI)+modified coal slag can reduce the sludge specific resistance, and the subsequent addition of Fe(III) has different degrees of influence on these three methods. When the dosage of Fe(III) was 40mgFe / gSS, the initial sludge specific resistance of Fe(III), Fe(III)+Fe(VI), Fe(III)+modified coal slag, Fe(III)+Fe(VI)+modified coal slag was reduced from 8.06×1012m / kg, 5.61×1012m / kg, 2.23×1012m / kg and 0.78×1012m / kg to 7.21×1012m / kg, 4.41×1012m / kg, 1.82×1012m / kg and 0.51×1012m / kg, respectively, down by 10%, 22%, 20% and 36%, respectively. Fe(III)+Fe(VI)+modified coal slag was the most affected. When the Fe(III) dosage is 100 mgFe / gSS, the sludge specific resistance after conditioning with four methods of Fe(III) alone, Fe(III) + Fe(VI), Fe(III) + modified coal slag, and Fe(III) + Fe(VI) + modified coal slag are 5.31×1012m / kg, 3.03×1012m / kg, 1.49×1012m / kg and 0.31×1012m / kg, respectively, down 34%, 47%, 56% and 62%.
[0043] With the increase of Fe(III) dosage, Fe(III)+Fe(VI)+modified coal slag has the best effect on improving sludge specific resistance, followed by Fe(III)+modified coal slag, and Fe(III)+Fe(VI) is slightly worse. This is because in the Fe(III)+Fe(VI) system, ferrate oxidizes and breaks down the extracellular polymer EPS, which weakens the ability of EPS to interfere with sludge dehydration, thereby promoting sludge dehydration; while in the Fe(III)+modified coal ash system, the flocculation of Fe(III) and the coagulant ability of modified coal ash are fully utilized, so that the strength of the newly generated sludge flocs is increased, and new water passages are generated around the modified coal ash. The number of flocs destroyed by shear force during mechanical dehydration is reduced, and the phenomenon of fine particles in the sludge blocking the filter pores is reduced, thereby reducing the filtration resistance and improving the filtration performance; the Fe(III)+Fe(VI)+modified coal ash system combines the reduction of EPS influence and the enhancement of sludge floc strength, which not only reduces the influence of organic matter on sludge dehydration, but also achieves the requirement of sludge reduction to a certain extent, making the sludge dehydration effect better. Therefore, the Fe(III)+Fe(VI)+modified coal ash system can be considered as an effective sludge conditioner combination.
[0044] After filtering and dehydration, the moisture content of the filter cake after the sludge conditioned by different dosing methods is as follows: Figure 8. With the increase of Fe(III) dosage, the moisture content of the sludge cake decreased after being conditioned by four different methods: Fe(III), Fe(III) + Fe(VI), Fe(III) + modified coal slag, and Fe(III) + Fe(VI) + modified coal slag. When the Fe(III) dosage was 40 mgFe / gSS, the four methods of Fe(III), Fe(III) + Fe(VI), Fe(III) + modified coal slag, and Fe(III) + Fe(VI) + modified coal slag reduced the initial sludge moisture content from 86%, 83%, 62% and 58% to 82%, 75%, 58% and 53% respectively. When the dosage of Fe(III) increases to 100 mgFe / gSS, the moisture content of the sludge after conditioning with four methods, namely, Fe(III), Fe(III)+Fe(VI), Fe(III)+modified coal slag, and Fe(III)+Fe(VI)+modified coal slag, drops to 76%, 71%, 53.8% and 47%, respectively. It can be seen that when conditioning with Fe(III) alone, the decrease in sludge moisture content is not particularly large. This may be due to the fact that the dosage of iron salt is too small, making it difficult to form good flocs and difficult to filter and dehydrate. When conditioning the sludge with Fe(III)+Fe(VI), the moisture content of the sludge decreases compared with that with Fe(III) alone. This is because ferrate can oxidize the extracellular polymer EPS, which releases interstitial water and reduces the influence of EPS on sludge dehydration. In addition, the newly generated hydrated iron oxide also has a good flocculation effect, which invisibly increases the coagulation intensity and enhances the dehydration effect. In the Fe(III)+modified coal ash system, the addition of modified coal ash greatly reduces the tax recovery rate of the mud cake. This is because after the modified coal ash and the sludge particles are electrically neutralized, the multipolymer after hydrolysis of Fe(III) is more likely to undergo adsorption and bridging with the combined action, destroying the stability of the sludge colloidal dispersion system, causing the small particles dispersed in the sludge to aggregate into larger particles. At the same time, the spherical structure of the coal ash increases the porosity of the filter layer and reduces the resistance to water removal from the mud cake. In the Fe(III)+Fe(VI)+modified coal ash system, after the addition of ferrate, EPS is broken, and the large particles of sludge flocs become smaller. The surface of the modified coal ash is rough and has strong adsorption. It enters the middle of these small flocs, releasing some interstitial water. In addition, the effect of EPS hindering sludge dehydration is reduced, and the sludge dehydration effect is more obvious. Therefore, the Fe(III)+Fe(VI)+modified coal ash system can effectively enhance the effect of sludge dehydration, but the dosage is too large. In the subsequent optimization of the system, multiple parameters should be considered comprehensively.
[0045] (3) The sedimentation effect of sludge can determine the size of sludge floc structure and whether the coagulant is within the effective dosage range. Strengthening the sedimentation effect of sludge can reduce the difficulty of mechanical dehydration and effectively reduce the water content of sludge. In (1), the effect of (III) alone on sludge dehydration is not particularly obvious, so the dosage of Fe (III) is appropriately increased, and compared with the combined addition of Fe (III) at a lower dosage, the sedimentation of the conditioned sludge is examined, and the change of sludge height within 100 minutes of sedimentation time is examined. At the same time, two groups of systems with different composite methods are selected for comparison.
[0046] Fig. 9The figure shows the effects of four different conditioning methods, namely, Fe(III), Fe(III) + Fe(VI), Fe(III) + modified coal slag, and Fe(III) + Fe(VI) + modified coal slag, on the sludge settling performance. It can be seen that as the sludge settling time increases, the sludge height gradually decreases, the volume of the sludge supernatant also increases, and the water content of the sludge concentration increases. When the sludge was conditioned with Fe(III) alone and the dosage was 60 mgFe / gSS, the sludge height accounted for 95.2% at 30 minutes of settling, and when the time was extended to 100 minutes, the sludge height accounted for 85.9%. As the settling time increases, the sludge height accounted for a slow decrease. When Fe(VI) was added to condition the sludge together with Fe(III), the dosage of Fe(III) and Fe(VI) was 60 mgFe / gSS and 3 mgFe / gSS respectively. After 30 minutes of sedimentation, the sludge height accounted for 93.8%. When the time was extended to 100 minutes, the sludge height accounted for 79%. The sludge sedimentation effect was enhanced, but the sedimentation interface was not particularly clear. This was because ferrate broke down the EPS in the sludge, reducing the effect of EPS on sludge sedimentation. However, some sludge floc particles were also broken to form a turbid sedimentation interface. In the Fe(III)+modified coal slag system, it was known in previous studies that modified coal slag has a great influence on sludge settling properties and can effectively improve the sludge settling effect. Therefore, the dosage of Fe(III) and modified coal slag was set to 20 mgFe / gSS and 30 g / L. When the settling time was 30 min, the sludge height accounted for 89%, and when the time was extended to 100 min, the sludge height accounted for 64%. As the settling time increased, the sludge height accounted for a rapid decrease, and the settling effect at this time was stronger than that of F. e(III) showed a significant sedimentation effect when 60 mgFe / gSS was added. This is because the adsorption energy of the modified coal slag increases, which produces an adsorption bridging effect in the sludge mixture, prompting the sludge particles to flocculate and bridge together after mutual collision after Fe(III) conditioning. At the same time, the modified coal slag can destroy the stable double-layer structure of the sludge colloidal particles, making the cohesion of the sludge particles dominant. The fine sludge particles flocculate with the iron salt hydrolyzed polymer into larger flocs, which are easy to settle, thereby improving the sedimentation performance of the sludge.
[0047] When Fe(III), Fe(VI) and modified coal slag are used to condition the sludge at the same time, the dosage is 20 mgFe / gSS, 3 mgFe / gSS and 30 g / L respectively. After 30 minutes of sedimentation, the sludge height accounts for 77.5%. The sedimentation effect at this time is equivalent to the effect of the Fe(III) + modified coal slag system after 60 minutes of sedimentation, which is 100 minutes for the Fe(III) + Fe(VI) system; when the time is extended to 60 minutes, the sludge height accounts for 65%, which is equivalent to the effect of the Fe(III) + modified coal slag system after 90 minutes of sedimentation; when the time is extended to 100 minutes, the sludge height accounts for 54%, and the sludge sedimentation efficiency slows down in the subsequent stage. In the Fe(III)+Fe(VI)+modified coal ash system, after pre-oxidation by ferrate, the extracellular polymers EPS in the sludge are broken down, and the lysis effect is obvious, which increases the soluble organic matter in the system. After the coal ash is modified, the chemical properties increase, the specific surface area and the reaction contact area become larger, and the adsorption performance is improved. It has an adsorption effect on the soluble organic matter in the sludge system, so that the soluble organic matter in the sludge system is separated from the surface of the sludge flocs, reducing the effect of organic matter on sludge sedimentation. At the same time, due to the relatively large density of coal ash, the density of the flocs is increased after the coal ash is wrapped in the flocs, the sedimentation rate of the floc particles is increased, and the sedimentation effect is obvious. The combination of the new ecological hydrated iron oxide generated by ferrate, the high polymer generated by the hydrolysis of iron salts, and the modified coal ash with a large specific surface area can effectively strengthen the aggregation of sludge floc particles and improve the sedimentation performance of sludge.
[0048] (4) The capillary absorption time (CST) of sludge refers to the time required for sludge water to penetrate a certain distance on the absorbent filter paper. It can be used to measure the sludge filtration performance and state. The sludge filtration performance determines the effect of different types of dewatering equipment. The larger the CST value, the worse the sludge dewatering performance, and vice versa. The CST value of sludge can intuitively reflect the destabilization of the sludge after conditioning, and can judge the flocculation superiority of the flocculant, so as to select the best flocculant and its concentration. The main focus is on the changes in the CST value of sludge after sludge pre-conditioning using four methods: Fe(III) alone, Fe(III) + Fe(VI), Fe(III) + modified coal slag, and Fe(III) + Fe(VI) + modified coal slag. From Fig.10It can be seen that the influence of four different addition methods, namely, Fe(III), Fe(III)+Fe(VI), Fe(III)+modified coal slag, and Fe(III)+Fe(VI)+modified coal slag, on the sludge CST value has a similar trend to the sludge specific resistance SRF, and shows a downward trend with the increase of Fe(III) addition. When the Fe(III) addition is 0, the combined addition of Fe(VI) and modified coal slag can further reduce the sludge CST value from the initial 80s to 43s, while the CST values of the sludge conditioned by Fe(VI) alone and modified coal slag alone are 46s and 60s, respectively. The effect of ferrate on reducing the sludge CST value is better than that of modified coal slag. When the Fe(III) dosage was 40 mgFe / gSS, the CST values of the sludge treated with Fe(III), Fe(III)+Fe(VI), Fe(III)+modified coal slag, and Fe(III)+Fe(VI)+modified coal slag decreased from the initial 80s, 46s, 60s, and 43s to 73s, 41s, 49s, and 36s, respectively. As the Fe(III) dosage increased, the decreasing trend of the sludge CST values treated with Fe(III)+Fe(VI), Fe(III)+modified coal slag, and Fe(III)+Fe(VI)+modified coal slag slowed down. At this time, the Fe(III) dosage was 80 mgFe / gSS, and the corresponding sludge CST values dropped to 67s, 38s, 45s, and 32s.
[0049] When Fe(III) is used alone to condition sludge, the CST value of sludge decreases less and more slowly, which indicates that the amount of flocculant added is too small to improve the dewatering performance of sludge, and the hydrolysis products of iron salts cannot use sludge particles as crystal nuclei, and due to the presence of extracellular polymers EPS, it is prevented from bridging with other small particles, and cannot play the role of sweeping net capture, and is suspended in the liquid to affect the coagulation effect, thereby affecting the dewatering performance of sludge. When Fe(VI) is added to condition sludge together with Fe(III), Fe(VI) can affect the sludge particle size and structure due to its strong oxidizing property, so that EPS breaks down, reduces the dewatering resistance formed by EPS wrapping sludge floc particles, releases interstitial water in sludge flocs, and strengthens the dewatering effect. At the same time, ferrate is reduced to a new ecological hydrated iron oxide after pre-conditioning, which has a higher specific surface area and can promote the aggregation of floc particles, thereby reducing the CST value of sludge. When modified coal slag is added to the sludge together with Fe(III), the positively charged silicon-aluminum active points wrapped by impurities in the modified coal slag are exposed on the particle surface, which can neutralize the negative charge on the sludge floc particles, making the sludge flocs destabilized. The chances of collision between small particle flocs and between them and the modified coal slag increase, forming large particle flocs that are easy to settle. However, the modified coal slag has limited effect on the EPS in the sludge, so the sludge settling effect is weaker than when Fe(VI) is added.
[0050] When the Fe(III)+Fe(VI)+modified coal ash system is used to condition the sludge, the ferrate oxidizes and breaks down the EPS, which weakens the effect of EPS on the modified coal ash. In addition, the modified coal ash also has a certain adsorption effect on the polysaccharides and proteins generated after the EPS is broken down, alleviating the adverse factor of increased sludge viscosity due to excessively high soluble protein and polysaccharide content. The sludge after comprehensive conditioning is easier to dehydrate.
[0051] Example 3
[0052] The inventors have found through research that using the multivalent iron salt composite modified coal ash provided in the present invention to condition sludge dehydration can further improve the sludge dehydration effect.
[0053] (1) Since different sludge conditioners have different structures and modes of action, different dosing orders may lead to different conditioning results when used in combination. Therefore, the effect of dosing order when ferrate and modified coal slag are used in combination is mainly investigated. There are three different dosing methods for ferrate and modified coal slag:
[0054] 1. First add modified coal slag and stir to mix, then add ferrate, and finally add Fe(III) and stir to mix;
[0055] 2. Ferrate and modified coal slag are added to the sludge at the same time, and then stirred and mixed after adding Fe(III);
[0056] 3. First add ferrate and mix well, then add Fe(III), and then add modified coal slag and mix well.
[0057] from Fig.11 It can be seen that the changes in the specific resistance of the sludge after conditioning are different under the three different dosing methods. When Fe(III) is not added, the specific resistance of the sludge after conditioning by methods 1, 2 and 3 are 1.53×1012m / kg, 0.77×1012m / kg and 2.15×1012m / kg respectively. The first addition of ferrate can reduce the SRF of the sludge the most, followed by simultaneous addition, and the first addition of modified coal slag ranks last. When Fe(III) was added, the SRF of the sludge was reduced to a certain extent by the three addition methods. When the Fe(III) dosage was 40 mgFe / gSS, the SRF of the sludge after conditioning by method 1, method 2 and method 3 was reduced to 1.01×1012m / kg, 0.5×1012m / kg and 1.76×1012m / kg, and the specific resistance of the sludge was reduced. When the Fe(III) dosage was increased to 100 mgFe / gSS, the SRF of the sludge after conditioning by method 1, method 2 and method 3 was reduced to 0.43×1012m / kg, 0.2×1012m / kg and 1.01×1012m / kg, respectively. Under the influence of Fe(III), the specific resistance of the sludge was further reduced. Ferrate is added first, which can fully contact and oxidize the extracellular polymer EPS in the sludge, break it and release bound water, reducing its impact on the subsequent Fe(III) hydrolysis. The modified coal slag is added to the sludge system for conditioning at this time, which can effectively destabilize some of the broken sludge flocs again for sedimentation, giving full play to the oxidation effect of ferrate and the electrostatic neutralization effect of modified coal slag. When the modified coal slag is added first, although the sludge has begun to destabilize and aggregate and settle with the modified coal slag as the core, the subsequent addition of ferrate will destroy this trend. Although it also has a certain effect, it is not as good as when ferrate is added first. Therefore, when ferrate is added first, the conditioned sludge has the smallest specific resistance, the fastest filtration speed, and the shortest filtration time.
[0058] Fig.12The superiority of different dosing sequences was investigated from the change of sludge SCOD, where ΔSCOD = SCOD measured - SCOD initial. It can be seen that under the three different dosing methods, the change of SCOD of sludge gradually decreases with the increase of Fe(III) dosage. When Fe(III) is not added, the change of SCOD of sludge after conditioning by method 1, method 2 and method 3 is 2.31g / L, 2.72g / L and 1.72g / L respectively. The first addition of ferrate can make the change of sludge SCOD the largest, followed by simultaneous addition, and the first addition of modified coal slag ranks last. This is because when ferrate is first added, it comes into contact with the floc particles in the sludge and can fully and effectively exert its lytic effect, releasing the SCOD therein, thereby increasing the SCOD content in the sludge supernatant. Although the modified coal slag added subsequently has a certain adsorption and removal effect on the organic matter in the sludge supernatant, compared with the amount released after oxidation by ferrate, the effect is very limited; and when the modified coal slag is added in advance, the sludge flocs aggregate and settle, and the contact opportunity of the ferrate added later with the sludge flocs is relatively reduced, and the oxidation effect will also be weakened accordingly, which makes the change in SCOD in the sludge supernatant smaller than the change in SCOD when ferrate is added in advance.
[0059] As the amount of Fe(III) added to the sludge system increases, the change in SCOD in the sludge supernatant gradually decreases. This is because the conditioning of Fe(III) also has a certain removal effect on SCOD in the sludge system. When the Fe(III) dosage is 40 mgFe / gSS, the change in SCOD of the sludge after conditioning by methods 1, 2 and 3 decreases from the initial 2.31 g / L, 2.72 g / L, 1.72 g / L to 1.74 g / L, 2.15 g / L, 1.56 g / L, and when the Fe(III) dosage increases to 100 mgFe / gSS, the change in SCOD of the sludge after conditioning by methods 1, 2 and 3 decreases by 1.42 g / L, 1.74 g / L, 1.23 g / L. It can be seen that Fe(III) has a certain removal effect on SCOD in the sludge supernatant. The polymer formed after the hydrolysis of Fe(III) can adsorb organic matter and wrap it together with the sludge floc particles, which reduces the SCOD content in the supernatant. When ferrate is added last, the change in ΔSCOD is the smallest. This is because ferrate is added in the later stage, and the SCOD content released is relatively reduced, which reduces the base number of removable SCOD content in the sludge supernatant, resulting in a weakened effect of Fe(III) coagulation removal.
[0060] From the above, it can be seen that the priority addition of ferrate can not only enhance the effect of reducing the specific resistance of sludge, but also enhance the release of SCOD after ferrate is broken into sludge, thereby affecting the effect of EPS in flocs on sludge dewatering. Therefore, according to the addition method of method 2, ferrate is added first and mixed, then Fe(III) is added, and then modified coal slag is added and mixed. This method is selected as the best addition order.
[0061] (2) The combined effect of ferrate and modified coal slag can effectively promote the dewatering performance of sludge. At this time, the dosage of ferrate and modified coal slag is 0.4mgFe / gSS and 30g / L respectively. This dosage is the optimal dosage for conditioning sludge with ferrate alone and modified coal slag alone. At this time, the dosage of modified coal slag is the determining factor of the final mud cake weight. Therefore, when ferrate and modified coal slag are added together, the dosage of modified coal slag should be appropriately reduced while ensuring a certain dehydration effect. Adjusting the dosage of ferrate and iron salt can reduce the weight of the mud cake and provide a convenient prerequisite for the subsequent treatment and disposal of sludge. The influence of iron salt on sludge dewatering performance under different dosages of ferrate and modified coal slag is now investigated. The dosage of ferrate was selected as 1.5 mgFe / gSS and 3 mgFe / gSS, while the dosage of modified coal slag was selected as 15 g / L and 30 g / L, respectively. The changes in the sludge specific resistance after conditioning at these two dosages were investigated.
[0062] Fig.13 It shows the change of sludge specific resistance after conditioning under different combinations of ferrate and modified coal slag. When Fe(III) is not added, the influence of different combinations of ferrate and modified coal slag on sludge specific resistance is also different. Fe(VI)1.5+ modified coal slag 15 and Fe(VI)1.5+ modified coal slag 30 reduce the initial specific resistance of sludge from 8×1012m / kg to 4.12×1012m / kg and 1.25×1012m / kg, respectively, while Fe(VI)3+ modified coal slag 15 and Fe(VI)3+ modified coal slag 30 reduce the specific resistance of sludge to 2.37×1012m / kg and 0.78×1012m / kg. It can be seen that the change in the dosage of modified coal slag has a greater impact on the sludge specific resistance, which is the same as the experimental results in the previous two chapters. This is because although ferrate can reduce the impact of EPS extracellular polymers, the proteins and polysaccharides generated after floc oxidation and decomposition dissolve in the solution, increasing the viscosity of the sludge solution and forming a certain resistance to sludge dehydration. When modifying sludge, the specific resistance of sludge can be effectively reduced by adsorbing soluble organic matter, neutralizing static electricity, adsorbing bridging and building a permeable skeleton, but the dosage will also increase accordingly, and the weight of the mud cake will also increase.
[0063] When Fe(III) is added to the sludge system alone, the specific resistance of the conditioned sludge gradually decreases with the increase of the dosage. When it is used together with different dosages of ferrate and modified coal slag to condition the sludge, it also has a corresponding promoting effect. When the dosage of Fe(III) is 60mgFe / gSS, the specific resistance of the conditioned sludge under the four dosage combinations of Fe(III)+Fe(VI)1.5+modified coal slag 15, Fe(III)+Fe(VI)1.5+modified coal slag 30, Fe(III)+Fe(VI)3+modified coal slag 15, and Fe(III)+Fe(VI)3+modified coal slag 30 are 2.32×1012m / kg, 0.68×1012m / kg, 0.98×1012m / kg and 0.42×1012m / kg respectively. Compared with Fe(VI)3+modified coal slag 30, the combination of Fe(III)+Fe(VI)3+modified coal slag 15 decreased the specific resistance of the sludge by 13%, and the dosage of modified coal slag was reduced by 50%. At this time, the dosage of Fe(III) was 60mgFe / gSS, and the effect on the weight of the mud cake was much smaller than that of the modified coal slag. With the further addition of Fe(III), the changes in the specific resistance of the sludge after conditioning with the three dosage combinations of Fe(III)+Fe(VI)1.5+modified coal slag 30, Fe(III)+Fe(VI)3+modified coal slag 15, and Fe(III)+Fe(VI)3+modified coal slag 30 were not particularly large, and the influence of the Fe(III) dosage was small. It can be seen that the appropriate addition of Fe(III) can reduce the amount of modified coal slag. To a certain extent, the polymer after the hydrolysis of Fe(III) plays a bridging co-precipitation role, making the sludge floc particles larger. The new ecological hydrated iron oxide generated after the oxidation of Fe(VI) can also work together with the polymer to reduce the sludge specific resistance and improve the dewatering performance. Therefore, the composite technology of multivalent iron salts and the synergistic addition of modified coal slag have a good promoting effect on the specific resistance and sedimentation of sludge compared with the composite addition of ferrate and modified coal slag.
[0064] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including combining various technical features in any other appropriate manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A sludge dehydration method based on modified coal slag coupled with multivalent iron salt, characterized in that: Includes ferrate and modified coal slag.
2. A sludge dehydration method based on modified coal ash coupled with multivalent iron salt according to claim 1, characterized in that: After acid-modified coal slag orthogonal experiment, the acid concentration was 4 mol / L, the acid-ash ratio was 3:1 ml / g, and the acid leaching time was 3 h. The coal slag obtained was used to condition sludge dehydration, and the obtained sludge specific resistance was the smallest, which was 0.16×1013 m / kg. After alkali modification, the coal slag orthogonal experiment was carried out. The alkali concentration was 4 mol / L, the alkali-ash ratio was 3:1 ml / g, and the alkali leaching time was 3 h. The coal slag obtained was used to condition sludge dehydration, and the obtained sludge specific resistance was the smallest, which was 0.21×1013 m / kg. This is the optimal modification condition.
3. A sludge dehydration method based on modified coal slag coupled with multivalent iron salt according to claim 1, characterized in that: The specific surface areas of the two types of coal slag (original coal slag and alkali-modified coal slag) were measured by a specific surface area analyzer to be 16.7 m 2 / g, 58.9m 2 / , after the sludge is conditioned by the modified coal slag, the mixed sludge sample is subjected to constant pressure filtration and dehydration under a vacuum degree of 0.03MPa. The settling performance of the sludge conditioned by the modified coal slag is determined by the change in the sludge height within the settling time of 100min.
4. A sludge dehydration method based on modified coal slag coupled with multivalent iron salt, characterized in that: In order to study the pre-conditioning effect of ferrate on sludge of different properties, three representative sludge concentrations were selected:
1. SS = 4.5g / L (the sludge concentration in the aeration tank of the traditional activated sludge process is 4-5g / L); 2. SS = 12.5g / L (the sludge concentration in the secondary sedimentation tank of the traditional activated sludge process is 12-13g / L); 3. SS = 8.5g / L (a concentration between the two). The Fe(VI) dosage was 1mgFe / gSS, and the reaction time was 60min.
5. After the sludge was conditioned in four different ways, namely, Fe(III) alone, Fe(III) + Fe(VI), Fe(III) + modified coal slag, and Fe(III) + Fe(VI) + modified coal slag, the mixed sludge samples were dehydrated by constant pressure filtration under a vacuum degree of 0.08 MPa to investigate the changes in the sludge specific resistance.
6. The preparation method according to claim 5, characterized in that: The dosage of Fe(III) was appropriately increased, and compared with the combined addition of Fe(III) at a lower dosage, the settling properties of the conditioned sludge and the changes in sludge height within 100 minutes of settling time were investigated.
7. The preparation method according to claim 5, characterized in that: Changes in CST value of sludge after sludge pre-conditioning by four methods: Fe(III) alone, Fe(III) + Fe(VI), Fe(III) + modified coal slag, and Fe(III) + Fe(VI) + modified coal slag.
8. A sludge dewatering method based on modified coal slag coupled with multivalent iron salt, characterized in that: When ferrate is used in combination with modified coal slag for conditioning, there are three different ways of adding ferrate and modified coal slag. Way 1: first add the modified coal slag and stir and mix, then add ferrate, and finally add Fe(III) and stir and mix; Way 2: ferrate and modified coal slag are added to the sludge at the same time, and then stir and mix after adding Fe(III); Way 3: first add ferrate and mix, then add Fe(III), and then add modified coal slag and stir and mix, and record the changes in sludge specific resistance after conditioning with three different adding methods.
9. The preparation method according to claim 8, characterized in that: Under different dosages of ferrate and modified coal slag, the dosage of ferrate was selected as 1.5 mgFe / gSS and 3 mgFe / gSS, respectively, and the dosage of modified coal slag was selected as 15 g / L and 30 g / L, respectively. The changes in the sludge specific resistance after conditioning at these two dosages were investigated.
Citation Information
Patent Citations
Application of ferrate in municipal sludge conditioning
CN102583949A
Method for improving dehydration performance of residual sludge by assisting oxidization of ferrate by utilizing ultrasonic waves
CN103359908A
Combination type efficient sludge dewatering conditioning method
CN104891779A
Modification method for energy utilization of sludge or organic waste
CN105927986A
Papermaking sludge conditioning agent and application thereof
CN110981158A